Influence of financial regulation in Kenya on financial inclusion: A case study of the banking industry in Kenya - Deborah Kemunto Momany (Kenya Bankers Association (KBA), 2018)
The positive impact of financial inclusion on the lives of the citizens of African countries as well as their economies in the last decade is non-debatable. Subsequently, financial inclusion has greatly contributed to the diminishing number of the unbanked population in African countries especially with the advent of provision of digital financial services. Nonetheless, the population of adults lacking access and usage of financial services is above two (2) billion. Finance serves a primary purpose of facilitating productive economic activities in a country. Economic growth and financial stability is best achieved in an environment with sound financial regulations. Whereas financial systems across Africa have experienced profound changes as characterised by financial deepening and rapid growth in intermediation, there is a compelling need to ensure that the day-today economic activities are not marred by unsound financial environments. Though the changes have positively impacted financial inclusion and intermediation in Kenya, the Central Bank of Kenya is faced by a plethora of challenges in its effort of ensuring that the economy is thriving. This is besides ensuring that there is financial stability through the enforcement of compliance, regulation and supervision of financial institutions within the banking sector. This research paper discussed the influence of financial regulations in Kenya on financial inclusion in the context of the banking industry in Kenya This research took the nature of a survey. The population of the study on the side of the regulated institutions comprised all institutions licenced under the Banking Act. Data collection was by means of a questionnaire. The questionnaire was structured with open ended and closed ended questions. The open ended questions collect qualitative data whereas the closed ended collect quantitative data. Opinions, views and perceptions were captured through scaling questions. From the analysis of findings, a positive correlation was established between financial inclusion variables i.e quality, usage and access and financial stability of institutions regulated by the banking act. The study recommended that the government can also through its role in regulation create a regulatory framework that encourages financial inclusion in order to enhance financial stability.
Keywords: 330; Finanzmarktregulierung; Bankenliquidität; Finanzielle Inklusion; Bankgeschäft; Kenia